Changes in Cervical Alignment after Multilevel Schwab Grade II Thoracolumbar Osteotomies for Adult Spinal Deformity. Issue 2 (15th January 2018) - Ghobrial, George M.; Lebwohl, Nathan H.; Green, Barth A.; Gjolaj, Joseph P.
Abstract : Study Design: A retrospective cohort. Objective: The aim of this study was to describe changes in cervical alignment (CA) and cervical deformity (CD) after multilevel Schwab Grade II Osteotomies for adult spinal deformity (ASD). Summary of Background Data: Reciprocal cervical and global changes after ASD surgery have not been previously described in the setting of multilevel osteotomy. Methods: Patients with long-segment (> five levels) fusion and osteotomy for ASD were radiographically evaluated. Pre- and postoperative cervical parameters evaluated included cervical lordosis (CL), C2-C7 sagittal vertical axis (C2-C7 SVA), and the T1 slope (T1S) minus the CL (T1S-CL). CD was defined as C2-C7 SVA >4 cm, CL < 0°, or T1S-CL ≥15°. Results: Eighty-five patients (mean age 64 ± 11.1) were identified. Preoperative lumbar lordosis (LL) was 28.7° ± 13.8°, thoracic kyphosis (TK) was 28.2° ± 17.0°, C7 plumbline (C7 SVA) was 7.54 ± 6.7 cm, pelvic tilt (PT) was 30.0° ± 8.96°, lumbopelvic mismatch was 32° ± 17.1°, and the T1 pelvic angle (TPA) was 26.8° ± 12.9°. The C7 SVA and TPA corrected to 3.90 cm ( P  < 0.0001) and 17.5°, respectively ( P  < 0.0001). CD increased from 41 (48%) to 47 (55%) patients. The mean CL changed from 16.5° to 11.9° ( P  < 0.013), C2 SVA from 10.1 to 6.37 cm ( P  < 0.0001), T1S-CL from 10.2° to 14.3° ( P  = 0.021), and TK from 28° to 39° ( P  < 0.0001). A correlation was observed between T1S and CL (ρ = 0.435, P  < 0.0001) and C2-C7 SVA (ρ = 0.624, P  < 0.0001). T1S was the only independent predictor of both the postoperative C2-C7 SVA and CL. In this study, the presence of any single preoperative CD criterion was noted to be a risk for persistent global deformity on postoperative radiograph [odds ratio (OR) = 2.5] and the development of PJK (OR = 2.1). The T1-CL < 15° may indicate an even greater risk for persistent global deformity (OR = 3.5). Conclusion: Thoracolumbar fusion with multilevel Schwab Grade II Osteotomies was associated with a decreased CL and reciprocal increases in TK and T1S-CL. Level of Evidence: 3